Arterial Thoracic Outlet Syndrome Treated Successfully with Totally Endoscopic First Rib Resection - Sofoklis Mitsos; Davide Patrini; Sara Velo; Achilleas Antonopoulos; Martin Hayward; Robert S. George; David Lawrence; Nikolaos Panagiotopoulos (Case Reports in Pulmonology)
Thoracic outlet syndrome (TOS) is a constellation of signs and symptoms caused by compression of the neurovascular structures in the thoracic outlet. TOS may be classified as either neurogenic TOS (NTOS) or vascular TOS: venous TOS (VTOS) or arterial TOS (ATOS), depending on the specific structure being affected. The basis for the surgical treatment of TOS is resection of the first rib, and it may be combined with scalenectomy or cervical rib resection. Herein, we describe a case of arterial thoracic outlet syndrome which was successfully treated with totally endoscopic video-assisted thoracoscopic surgery (VATS) first rib resection.